Sustainability Disclosure: Salience Stakeholder Identification? - Rieka Ramadhaniyah; Nolita Yeni Siregar; Reva Meilina (Proceeding International Conference on Information Technology and Business, 2022)
This study aims to prove empirically whether stakeholder salience affects sustainability disclosure. Stakeholder salience variables consist of shareholders, government, creditors, mass media, local communities, suppliers, environment, and special interest groups, employees and consumers. The population used in this study are companies listed on the Indonesian Stock Exchange and consistently releasing sustainability reports in 2017-2020. The sampling technique in this study used a purposive sampling method with several criteria to obtain 147 samples. The test results prove that shareholders, government, creditors, mass media, local communities, suppliers, the environment, and special interest groups (NGOs) have no effect on the disclosure of sustainability reports, while employees and consumers affect the disclosure of sustainability reports.Keywords: Sustainability disclosure, Salience Stakeholder